MENGEMBANGKAN KOMPETENSI GURU DALAM PEMBELAJARAN BERDIFERENSIASI DI ERA REVOLUSI INDUSTRI 5.0 - Rufa hera; Rita Oktavia (Jurnal Bionatural, 2025)
This study aims to explore the development of teachers' competencies in implementing differentiated instruction in five high schools in Nagan Raya and West Aceh, involving 15 teachers with diverse teaching experience backgrounds. The findings indicate that 70% of the teachers understand the importance of differentiated instruction; however, only 45% feel confident in their ability to apply it effectively. Classroom observations revealed that only 50% of the teachers consistently use this strategy, while 80% reported having attended training, but only 40% felt they benefited from it. Major barriers included a lack of resources, learning aids, and the rigidity of the curriculum. Although most students reported feeling more motivated when this approach was implemented, challenges remain regarding the consistency of its application. Recommendations to enhance teachers' competencies include evaluating training programs, providing management support, and fostering collaboration among teachers. The results of this study emphasize the need for an integrated approach to maximize the effectiveness of differentiated instruction in the era of Industry 5.0.